Change Management Analysis Of â€œBerAKHLAKâ€ Policy at Government Owned Corporation - Andi Azikin Idrus; Djoko Triono; Rahmawati Rahmawati (Khazanah Sosial, 2024)
This research focuses on analyzing the basic values policy of "BerAKHLAK" or Trustworthiness, Competence, Harmony, Loyal, Adaptive and Collaboration at PT Kawasan Berikat Nusantara, which is one of the Government-Owned Corporation (BUMN). A case study approach is used in this research to describe how implementing these policies affects organizational change and HR performance in the company. Based on the in-depth interviews and documentation analysis that we conducted, we found that implementing BUMN's basic values can increase adaptability, collaboration, and employee performance, as well as optimize change management to achieve the company's strategic goals, to achieve the company's strategic goals. The conclusion underlines the importance of ethical value integrity in managing organizational change effectively and sustainably.